2009
DOI: 10.1038/ijo.2009.260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal educational level on the association between the rs3809508 neuromedin B gene polymorphism and the risk of obesity in the HELENA study

Abstract: Objective: Neuromedin B (NMB) is a bombesin-like peptide, which inhibits food intake and modulates stress-related behaviour. An NMB gene polymorphism (P73T) has been earlier associated with obesity and abnormal eating behaviour in adults. Methods: The association between four NMB polymorphisms and obesity-related phenotypes was investigated in the Healthy Lifestyle in Europe by Nutrition in Adolescence cross-sectional study (n ¼ 1144, 12-17-year-old European adolescents). This population was genotyped for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(65 reference statements)
2
19
0
Order By: Relevance
“…The statistical significance of this interaction remains when the GP and OHP samples are included in a joint analysis. Although there is ample evidence that educational level is an important environmental variable associated with obesity and cardiovascular risk [17], there have been scarcely any studies that have examined the interaction of this variable with the effects of genetic variability in determining BMI [1113], the exception being a recent publication by Holzapfel et al [34], that investigates the association between SNPs in the TMEM18 and FTO genes with educational level as well as income; however, the authors did not formally analyze the interaction between these SNPs and education in determining BMI and obesity, and we cannot compare our results with theirs [34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical significance of this interaction remains when the GP and OHP samples are included in a joint analysis. Although there is ample evidence that educational level is an important environmental variable associated with obesity and cardiovascular risk [17], there have been scarcely any studies that have examined the interaction of this variable with the effects of genetic variability in determining BMI [1113], the exception being a recent publication by Holzapfel et al [34], that investigates the association between SNPs in the TMEM18 and FTO genes with educational level as well as income; however, the authors did not formally analyze the interaction between these SNPs and education in determining BMI and obesity, and we cannot compare our results with theirs [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a study undertaken on Danish twins [12], investigated how genetic and environmental variance in physical health differed with level of education, and concluded that education reduced the influence of genetic susceptibility to poor health, suggesting that this might take place because more educated people manage their environments better to protect their health. Concerning the analysis of specific loci, there is one study showing that a low educational level aggravated the association between the rs3809508 neuromedin B single nucleotide polymorphism (SNP) and the risk of obesity in the HELENA study [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Two SNPs-rs1414839 y rs967790-in the gene encoding the NMBR have been associated with higher weight loss in patients undergoing Roux-en-Y gastric bypass surgery[118]. Furthermore, a rs3809508 polymorphism of the gene encoding the peptide NMB, as well as other mutations in the NMB gene, is associated with increased risk of obesity[119–121]. …”
Section: Brs-3 In Obesity; Energy and Glucose Homeostasis And Diabmentioning
confidence: 99%
“…Similarly, a variant of the APOA2 gene increases the association with obesity in those consuming high levels of saturated fatty acids [50]. Another study reported the influence of maternal education on the effect of a variant of the neuromedin B gene on obesity [19]. Based on these studies, we evaluated environments that conducive to possible interaction, such as social status, education, history of breastfeeding, and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Results in a Mediterranean population suggest that education may modify the genetic susceptibility of FTO to obesity, with BMI being higher in non-university subjects compared to university subjects [18]. On the other hand, Pigeyre et al [19] report the influence of maternal education in the association of neuromedin B rs3809508 and the risk of obesity. Perinatal conditions, such as increased or decreased fetal growth, as measured by weight and height at birth, or low breastfeeding, may also influence the likelihood of obesity later on in life [20].…”
Section: Introductionmentioning
confidence: 99%